Roberts syndrome in an Indian patient with humeroradial synostosis, congenital elbow contractures and a novel homozygous splice variant in ESCO2. Issue 11 (11th August 2020) - Schneeberger, Pauline E.; Nayak, Shalini S.; Fuchs, Sigrid; Kutsche, Kerstin; Girisha, Katta M.
Abstract: Roberts syndrome (also known as Roberts‐SC phocomelia syndrome) is an autosomal recessive developmental disorder, characterized by pre‐ and postnatal growth retardation, limb malformations including bilateral symmetric tetraphocomelia or mesomelia, and craniofacial dysmorphism. Biallelic loss‐of‐function variants in ESCO2, which codes for establishment of sister chromatid cohesion N‐acetyltransferase 2, cause Roberts syndrome. Phenotypic spectrum among patients is broad, challenging clinical diagnosis in mildly affected individuals. Here we report a 3‐year‐old boy with a mild phenotype of Roberts syndrome with bilateral elbow contractures, humeroradial synostosis, mild lower limb disparity, and facial dysmorphism. Trio whole‐exome sequencing identified the novel biallelic splice variant c.1673+1G>A in ESCO2 in the patient. Aberrant ESCO2 pre‐mRNA splicing, reduced relative ESCO2 mRNA amount, and characteristic cytogenetic defects, such as premature centromere separation, heterochromatin repulsion, and chromosome breaks, in patient cells strongly supported pathogenicity of the ESCO2 variant affecting one of the highly conserved guanine‐thymine dinucleotide of the donor splice site. Our case highlights the difficulty in establishing a clinical diagnosis in individuals with minor clinical features of Roberts syndrome and normal intellectual and social development. However, next‐generation sequencing tools allow for molecular diagnosis in cases presenting with mild developmental defects.